An Equilibrium Aggregate Demand and Supply Model to Examine the Dynamic Effect of Oil Price Shocks on Output and Inflation in Iran as an Oil Exporting Country - Barkordari, Sajjad; Fattahi, Maryam (Economy of Regions, 2017)
Iran is an oil exporting country in Middle East. The high share of the oil revenues in Iran is a serious economic problem. Due to the high dependency of Iran’s economy on oil revenues, oil price shocks have a determinant impact on macroeconomic variables. In this paper, we analyze the dynamic effects of oil price shocks and the aggregate supply and aggregate demand shocks on macroeconomic fluctuations in Iran. According to macroeconomic theory and aggregate demand and supply model in equilibrium, a structural vector autoregressive (VAR) model is applied to identify different structural shocks and further assess the relative contributions of different shocks on macroeconomic fluctuations, using a decomposition approach. The results show that oil price shocks have significant and positive effects on both output and inflation. Aggregate supply and aggregate demand shocks are the main causes of fluctuation in output and inflation, and moreover, the effect of aggregate supply shocks on output is permanent in the Iranian economy. On the base of this study results, we suggest the Iranian government should accelerate the economic reforms such as the finance system of state owned enterprises, the tax system, the cash subsidy distribution system, the allocation system of the government budget in national and provincial level, the financial and banking system, and so on. The suggested reforms aim to decrease in the share of oil revenues in the economy and protect the Iranian economy in the face of any exogenous and endogenous shocks.